An Exploration of Job Stress among Health Care Work Force - Dhuha Saad Ismael; Rohat Zada; Prabhu M (ACHSM, 2021)
Objectives: The aim of this study is unique and will be useful in elucidating the level and sources of job stress among nurses working in government and private sector health institutions in the Kurdistan Region. This research could be useful in developing future nursing and healthcare manpower planning policies. In this research work, the objective is to evaluate the job stress among hospital nurses in the Kurdistan region. The research part basically explains about work-related stress and how it is harmful to the health of the employees. Methods: With the help of questionnaires, the authors collected primary data from the nurses working in 34 public and 56 private hospitals all over the Kurdistan region. To collect the data author used a simple random sampling method. The proposed study is descriptive in nature and authors collected data from 252 staff nurses working in the Kurdistan region. To do the analysis author used statistical tools like descriptive statistics, mean, cluster, chi-square, and correspondence analysis. To analyses, the data author used statistical software package SPSS 28. Results: The results reveals that the ranking of four job stress domains like job factor, organizational factors, interpersonal relations factors and environmental factors. In that the interpersonal relations factors are ranked number one and the second rank is organizational factors third one is environmental factors and the last one is job factor.  Conclusions: In Kurdistan region hospital staff nurses stressed due to routine shift and poor organizational structure are mostly influenced on organizational factors that are why it's ranked number one among the four domains.